Clinical long-term outcome of septal myectomy for obstructive hypertrophic cardiomyopathy in infants. (27th October 2017) - Schleihauf, Julia; Cleuziou, Julie; Pabst von Ohain, Jelena; Meierhofer, Christian; Stern, Heiko; Shehu, Nerejda; Mkrtchyan, Naira; Kaltenecker, Emanuel; Kühn, Andreas; Nagdyman, Nicole; Hager, Alfred; Seidel, Heide; et al.
Abstract: OBJECTIVES: Surgical septal myectomy is performed to relieve left ventricular outflow tract narrowing in severe drug-refractory obstructive hypertrophic cardiomyopathy. The objective of this study was to assess the perioperative and long-term clinical outcome of this procedure performed during infancy. METHODS: Clinical, transthoracic echocardiographic, electrocardiographic, 24-h Holter, cardiopulmonary exercise test and genetic data were extracted by medical record review. A subset of patients underwent additional prospective detailed clinical evaluation including cardiac magnetic resonance imaging with contrast. RESULTS: Surgery was performed in 23 paediatric patients between 1978 and 2015 at the German Heart Centre Munich. Twelve patients had undergone surgery during infancy (≤ 1 year) (Group A), 11 between 1 and 18 years of age (Group B). The underlying genetic diagnosis was Noonan syndrome spectrum and non-syndromic hypertrophic cardiomyopathy. As compared to Group B, patients in Group A showed more concomitant cardiac procedures and received more homologous transfusions. One perioperative death occurred in Group A, and none in Group B. Two patients in Group A but no patient in Group B required redo septal myectomy. The long-term clinical outcome was similar between the 2 groups. One patient in Group B required cardioverter–defibrillator/pacemaker implantation for higher degree atrioventricular block and none in Group A. There was no evidence of differences in myocardial fibrosis between groups on long-term follow-up magnetic resonance imaging. CONCLUSIONS: Surgical septal myectomy can be performed safely during infancy with favourable perioperative and long-term clinical outcome but with a trend towards a higher reoperation rate later in life.